(untitled) (Biodiversitas Journal of Biological Diversity, 2017)
Abstract. Sulistyo B. 2017. The accuracy of the outer boundary delineation of coral reef area derived from the analysis of various vegetation indices of satellite Landsat thematic mapper. Biodiversitas 18: 351-358. This research aimed at determining the accuracy of the outer boundary delineation of coral reef area derived from the analysis of various vegetation indices of satellite Landsat Thematic Mapper in Enggano Island, the District of North Bengkulu, Bengkulu Province. The vegetation indices of Landsat Thematic Mapper analyzed were the Ratio Vegetation Index, the Normalized Difference Vegetation Index, the Soil Adjusted Vegetation Index, the Transformed Soil Adjusted Vegetation Index, the Modified Soil Adjusted Vegetation Index and the Transformed Vegetation Index. The result of every analysis of vegetation index (index map) was then used as a base for on-screen digitization of the points assumed to be the outer boundary of coral reefs in order to get digital data. Digitization of shoreline was also done to create an inner boundary of coral reefs. When it is combined with its outer boundary then the calculation of the area is possible. The accuracy of the result was validated by overlaying it onto Map of Coral Reefs derived from a topographic map of Joint Operation Group. To justify whether the accuracy is good (or accepted) or not good (or not accepted), a threshold value proposed by Justice and Townshend was chosen, those are Poor (when the accuracy is < 70%), Moderate (when the accuracy is between 70% and 85%), and Good (when the accuracy is â‰¥ 85%). The results of the research showed that the accuracy of RVI and NDVI values were Poor, those are 67.11% and 66.42%, respectively, so it could not be used for further analysis. The other results were Moderate, those are 73.33% for SAVI, 74.22% for TSAVI, 77.32 % for MSAVI and 77.33% for TVI, and may be used as a quick alternative when the map is absent. Keywords: coral reefs, Landsat, outer boundary delineation, vegetation index